Effect of methoxy position on dynamic mechanical and shape memory properties of methoxyphenol-based polybenzoxazines. Issue 6 (17th July 2020) - Lu, Guosheng; Yang, Huiyun; Zhen, Hecheng; Li, Cuiyun; Shen, Shanshan; Liu, Yanfang; Run, Mingtao
Abstract: Two series of benzoxazines were synthesized from o -, m -, and p -methoxyphenols, two polyetheramines with different molecular weights, and formaldehyde. The glass transition temperatures ( T g s) of m -methoxyphenol-based polybenzoxazines are respectively higher than those of o - and p -methoxyphenol-based counterparts. The polybenzoxazines exhibit thermally induced one-way dual-shape memory behavior based on T g, and the o - and p -methoxyphenol-based polybenzoxazines exhibit higher shape memory performance than m -methoxyphenol-based counterparts under motion constraints.